2021
DOI: 10.3389/fmicb.2021.636344
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics and Comparative Secretome Analysis of Morchella importuna Grown on Glucose, Rice Straw, Sawdust, Wheat Grain, and MIX Substrates

Abstract: Morels (Morchella sp.) are economically important edible macro-fungi, which can grow on various synthetic or semi-synthetic media. However, the complex nutritional metabolism and requirements of these fungi remain ill-defined. This study, based on the plant biomass commonly used in the artificial cultivation of morels, assessed and compared the growth characteristics and extracellular enzymes of Morchella importuna cultivated on glucose, rice straw, sawdust, wheat grain, and a mixture of equal proportions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Morchella spp. strains are able to easily use a variety of sugars with low molecular weight, but it is more difficult for them to use more complex compounds, such as lignin and cellulose [ 23 ]. In low-fertility cultivation conditions, the growth of vegetative hyphae depended entirely on the nutrients contained in basic culture media or the original inoculation blocks, and the hyphae were weak and unable to form mitospores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morchella spp. strains are able to easily use a variety of sugars with low molecular weight, but it is more difficult for them to use more complex compounds, such as lignin and cellulose [ 23 ]. In low-fertility cultivation conditions, the growth of vegetative hyphae depended entirely on the nutrients contained in basic culture media or the original inoculation blocks, and the hyphae were weak and unable to form mitospores.…”
Section: Discussionmentioning
confidence: 99%
“…For example, indoor cultivation in the United States has stagnated after a period of operation, and field cultivation in China has recently also suffered 70% non-profit situations in some areas [ 9 , 10 , 11 , 12 ]. As a consequence, there has recently been a comprehensive promotion of field cultivation based on deep knowledge development of basic biological foundations, such as the identification and characteristics of cultivable varieties [ 12 , 13 , 14 , 15 ], the identification of mating type genes [ 9 , 10 ], the characteristics of heterokaryons [ 16 , 17 , 18 , 19 , 20 , 21 ], nutritional metabolism [ 22 , 23 ] and “omics” technology [ 19 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, key questions related to the life cycle of Morchella remain far from completely understood [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. importuna substrate preparation is crucial since our research has shown that it requires varied quantities of nutrients at different phases of growth. Researchers from the past have made similar observations on various growing substrates, they documented varying mycelial growth rates, levels of sclerotial formation, and so on(Cai et al 2021). .…”
mentioning
confidence: 93%
“…importuna since 2012 [ 1 , 3 ]. Recent progresses have focused on species classification [ 8 , 9 ], genetic development [ 10 , 11 , 12 , 13 ], life cycle [ 2 , 14 ], nutritional metabolism [ 13 , 15 , 16 ] and multiomics [ 10 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], but less on cultivation management. Nevertheless, ~70% of the growers were unable to make a steady profit, mainly due to a lack of understanding in species cognition, mating type, growth and development, physiology and nutrition, and field management.…”
Section: Introductionmentioning
confidence: 99%